MODEL SISTEM INSTITUSI MADRASAH NIDZAMIYAH DI ERA DINASTI SALJUK - Athoillah, Sukijan (Al-Fikri: Jurnal Studi dan Penelitian Pendidikan Islam, 2020)
This research discusses a model of the Nidzamiyah madarasah institutional system during the reign of the Seljuq dynasty. The system model includes characteristics, mission, curriculum, remuneration system for teachers, students and teachers, and socio-political aspects. This research uses a descriptive qualitative approach. The type of research is library research. Data collection techniques in this study used the documentation method to review madrasah documents related to the learning process of child labor. The results of this study indicate that madrasas in the Saljuk Dynasty were the highest educational institutions. However, madrasas cannot be equated with universities, because madrasah have different characteristics. The characteristics of madrasah that differentiate them from universities can be seen from the curriculum, conditions of teachers and students, as well as socio-political nuances.Keywords: Model, Madrasah Nidzamiyah, Seljuq Dynasty